A comparative study of polylactic acid (PLA)-Based unidirectional green hybrid composites reinforced with natural fibers such as kenaf, bamboo and coir - Rosni Binti Yusoff; Hitoshi Takagi; Antonio Norio Nakagaito (Hybrid Advances, 2023)
Plant-based composites are considered as new generation materials that offer sustainability, eco-friendly and green chemistry, utilized by numerous sectors. Composites of green hybrid made from polylactic acid (PLA) and three different plant fibers were prepared using two symmetrical fibers stacking sequences; namely high modulus and brittle (HMB) fibers (kenaf-bamboo-coir/PLA) and low modulus and ductile (LMD) fibers (coir-bamboo-kenaf/PLA) in the outmost layers. The stacking sequence was prepared using a simple slot tool to properly align the fibers and it was dried at 50 °C before being compressed using hot press. It was found that the tensile strength and tensile modulus of both hybrid composites increased linearly up to 158 MPa and 7 GPa respectively. It shows that the stacking sequences had no significant effect on tensile strength, but fracture strain increased by 58% produced by LMD fibres. However, the use of HMB fibres in the outmost layers significantly improved flexural strength up to 49% higher than that of LMD fibres. In contrast, the impact strength of the green hybrid composites using LMD fibres in the outmost layers was 21% higher than that of its counterpart. Like other plant fiber composites, both composites had an increased water absorption capacity of up to 39% due to increased fibre content. These stacking sequence properties are essential to fabricate a specific application to ensure properties suitable for the job's features. High modulus and brittle composites require a high load to deform permanently, as well as low modulus and ductile composites. Both exhibit versatile mechanical characteristic, providing a balance of sealant toughness and the ability to retain overall shape, such as in sound absorption and vibration in transportation.